(untitled) (The International Journal for Scientific Research, 2023)
Education has a crucial role in the development and self-realization of the individual, especially for the development of society. This is closely related to the quality of education provided to members of society. Education is one of the processes that aims to influence learners to be able to adapt themselves to their environment. This will cause change and allow them to function powerfully in the life of the society. Information and Communication Technology (ICT) along with the Internet has brought about progress and growth in banking, transportation, economy and most importantly in education. In the 21st century, individuals need a wide range of abilities, competencies and skills to adapt to the technological age. Possessing digital literacy requires more than just the ability to use software or operate a digital device; it includes a wide variety of complex skills such as cognitive, motor, social, and emotional that users need in order to use digital environments effectively. The conceptual model recently described by the authors suggests that digital literacy includes five key digital skills: visual imagery skills (“reading” instructions from graphical presentations), reproduction skills (using digital reproduction to create new and meaningful materials from pre-existing skills), branching skills (building knowledge from nonlinear, hypertextual navigation), information skills (evaluating the quality and validity of information), and social and emotional skills. In order to achieve these skills, the curriculum ensures the use of technological tools and strategies to provide teaching and learning strategies for learners. Digital literacy skills are essential for developing as independent learners in the digital age. Previous studies have shown that digital literacy skills have a positive impact on student performance. However, limited studies have been conducted on the issue. This paper presents a literature review of the increasing importance of ICT digital literacy skills to support teaching and learning.